Comparison of the use of social media in marketing by big and small enterprises in Poland - Samek, Katarzyna (Porównanie używania mediów społecznościowych w marketingu przez duże i małe firmy w Polsce, 2018)
The rapid and continuous development of new technologies at the turn of the 20th and 21st century and the ever-growing importance of the Internet allow companies to change the rules of competition in many sectors. The Internet has proven to be an effective tool for improving market position and at the same time has become an indispensable tool for communicating with customers. Opinions on businesses and goods or services offered are formed by online communities, and market position is built on comments posted by Internet users. The purpose of this article is to identify the types and examples of social media used for internet marketing by WIG30 companies and NewConnect companies. The study used the netnography method (virtual entrainment) and was conducted among twenty listed companies in Poland. The results show that the WIG30-listed companies are companies with a strong market position and a large number of loyal customers. However, they do not turn their back on social media and utilise more than five examples of them. On the other hand, the smaller NewConnect-listed companies are less recognizable among customers, so they should strive to establish interactions with online communities, using more social media for that purpose
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 2 (48), s. 67-76
Keywords: social media; Internet marketing; marketing; media społecznościowe; iinternet